A postmodern look at five of Huzir Sulaiman's plays - Mohd Azril, Adnan (University Malaysia Sarawak, UNIMAS., 2009)
The study was designed to examine five of Huzir Sulaiman’s plays from the perspective of the postmodern theory by looking at the issues of reality and representations of reality found in his works. The objectives is first, to examine whether Huzir Sulaiman’s plays fit into the postmodern framework based on selected elements of Postmodernism namely fragmentation, experimentation, rejection of meta-narratives, pastiche and streams of consciousness. The second objective is to analyze specific characteristics from the five plays in comparison to Baudrillard’s four stages of simulacra and simulations. Data was collected by selecting Huzir Sulaiman’s plays by using two criteria, first was that the plays chosen have characteristics of a postmodern literature, specifically elements of postmodernism. Second, the plays deal with postmodern issues, such as loss of reality, hyperreality and representations which can be categorized in Baudrillard’s four stages of simulacra and simulations. The plays were then read and analyzed based on the mentioned categories by using data analysis with the use of the postmodern theory as the framework. The findings showed that his plays can be termed as postmodern products as all five plays contains at least two of the postmodern elements and one of Baudrillard’s stages of simulacra and simulations. The results also showed that Sulaiman’s plays reflected the issues of the postmodern society such as issues of determining authenticity of reality and representations of reality in the society.